Systemic therapy of skin metastatic melanoma with BRAF gene mutation - Yu. S. Shakh-Paronyants; S. V. Cheporov; N. P. Shiryaev; A. V. Ukgarskiy; P. V. Nesterov; N. S. Korzina (Исследования и практика в медицине)
Purpose of the study. To conduct a comparative analysis of the effectiveness of the use of mono‑mode immuno‑oncological and targeted drugs in the first line of therapy in patients with metastatic melanoma of the skin (SMM) in patients with BRAF mutation.Patients and methods. To achieve this goal, a retrospective analysis of the treatment results was carried out in 61 patients diagnosed with metastatic melanoma of the skin and the presence of a mutation in the BRAF gene who were treated at the Yaroslavl regional oncology hospital. The patients were divided into two groups: the first group (n = 18) included patients who received mono‑mode immunotherapy in the first line of treatment; the second group (n = 43) included patients who underwent targeted first-line therapy.Standard regimens of monotherapy with BRAF inhibitors (vemurafenib, dabrafenib) or combination therapy with BRAF and MEK inhibitors (dabrafenib + trametinib) were chosen as treatment. Immunotherapy was performed using the following drugs: pembrolizumab, nivolumab and prolgolimab. An intergroup comparative analysis of one‑year, three‑year and five‑year survival rates was carried out. Progression‑free survival rates and the frequency of objective responses were also studied.Results. The median follow–up period in the first group was 14.2 months, in the second – 15.7 months. The indicators of one‑year, three-year and five‑year overall survival in patients receiving immunotherapy in the first line were 88.8 %, 55.5 % and 33.3 %, respectively. The same indicators in patients in the first‑line targeted therapy group were 90.7 %, 46.5 % and 23.2 %, respectively. The median overall survival in the first group was 39.1 months, in the second group it was 30.4 months. Progression–free survival in the group of patients with targeted therapy was 8.7 months, in the immunotherapy group – 9.8 months. In the first group, stabilization of the disease was observed in 77.8 % of patients, while a complete response was noted in 5.6 %, a partial response was not registered. In the second group of patients, stabilization was noted in 39.6 % of patients, partial response in 25.6 % of patients, complete response was absent.Conclusion. The use of cancer immunotherapy drugs in the first line of treatment in patients with metastatic melanoma of the skin and the presence of BRAF mutation in the short term is not inferior in effectiveness to the use of targeted drugs, and in the medium and long term exceeds targeted drugs.